Wissen Formen : Performative Akte zwischen Bildung, Wissenschaft und Kunst : Erkundungen mit dem Theater der Versammlung (Theater, 2018)
What happens when the language of the sciences meets that of the performing arts? Impulses for innovative academic teachings.
Keywords: Theater; Philosophie; Intermedialität; Performativity; Education; Performance Studies; Science; Art; Kunst; Wissenschaft; Sociology of Science; Fine Arts